2020
DOI: 10.7717/peerj.10054
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Gull-billed tern (Gelochelidon nilotica) nest survival in artificial coastal saltpans, Bohai Bay, China

Abstract: Background Coastal saltpans are a common supratidal human-modified wetland habitat found within many coastal landscape mosaics. Commercial salt production and aquaculture practices often result in the creation of exposed coastal substrates that could provide suitable breeding habitat for waterbird populations; however, few studies have quantified waterbird breeding success in these artificial wetlands. Methods Here we examine the nesting be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Flooding and abandonment were the main causes of nest failure. In comparison with other waterbirds breeding in the Nanpu saltpans, this nest survival was much higher than that of Kentish plover (Que et al, 2015) but lower than that in gull-billed tern (Wu et al, 2020), both of which were also estimated in the Nanpu saltpans but at different sites. These differences may be due to the different human disturbance levels occurring within the Nanpu saltpans.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Flooding and abandonment were the main causes of nest failure. In comparison with other waterbirds breeding in the Nanpu saltpans, this nest survival was much higher than that of Kentish plover (Que et al, 2015) but lower than that in gull-billed tern (Wu et al, 2020), both of which were also estimated in the Nanpu saltpans but at different sites. These differences may be due to the different human disturbance levels occurring within the Nanpu saltpans.…”
Section: Discussionmentioning
confidence: 55%
“…Research on Kentish plover (Charadrius lexandrinus) breeding in saltpans located in the EAAF showed that its nest survival was among the lowest reported for this species, and human disturbance was the main cause of nest failure (Que et al, 2015). Surprisingly, gull-billed tern (Gelochelidon nilotica) breeding in these saltpans had higher nest survival than previously published estimates from other regions (Wu et al, 2020). The relative strength of the factors shaping breeding success for ground-nesting waterbirds will vary according to the geographical position of saltpans on the flyways.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations